SNAP‐23 and VAMP‐3 contribute to the release of IL‐6 and TNFα from a human synovial sarcoma cell line. (13th December 2013) - Boddul, Sanjay V.; Meng, Jianghui; Dolly, James Oliver; Wang, Jiafu
<x xml:space="preserve">Abstract</x> Fibroblast‐like synoviocytes are important mediators of inflammatory joint damage in arthritis through the release of cytokines, but it is unknown whether their exocytosis from these particular cells is SNARE‐dependent. Here, the complement of soluble N‐ethylmaleimide‐sensitive factor attachment protein receptors (SNAREs) in human synovial sarcoma cells (SW982) was examined with respect to the secretion of interleukin‐6 (IL‐6) and tumour necrosis factor α (TNFα), before and after knockdown of a synaptosome‐associated protein of molecular mass 23 kDa (SNAP‐23) or the vesicle‐associated membrane protein 3 (VAMP‐3). Wild‐type SW982 cells expressed SNAP‐23, VAMP‐3, syntaxin isoforms 2–4 and synaptic vesicle protein 2C (SV2C). These cells showed Ca2+‐dependent secretion of IL‐6 and TNFα when stimulated by interleukin‐1β (IL‐1β) or in combination with K+ depolarization. Specific knockdown of SNAP‐23 or VAMP‐3 decreased the exocytosis of IL‐6 and TNFα; the reduced expression of SNAP‐23 caused accumulation of SV2 in the peri‐nuclear area. A monoclonal antibody specific for VAMP‐3 precipitated SNAP‐23 and syntaxin‐2 (and syntaxin‐3 to a lesser extent). The formation of SDS‐resistant complexes by SNAP‐23 and VAMP‐3 was reduced upon knockdown of SNAP‐23. Although the syntaxin isoforms 2, 3 and 4 are expressed in SW982 cells, knockdown of each did not affect the release of cytokines. Collectively, these results show that SNAP‐23 and VAMP‐3 participate in IL‐1β‐induced Ca2+‐dependent release of IL‐6 and TNFα from SW982 cells. Structured digital abstract VAMP-3 physically interacts with syntaxin 2 and SNAP-23 by anti-bait coimmunoprecipitation (View interaction)